2018
DOI: 10.1016/j.jobcr.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing perceptions of oral health related quality of life in dental implant patients. Experience of a tertiary care center in India

Abstract: Assessing quality of life with regards to specific treatment interventions may help to draw critical inferences that determine overall success. Results from the study enabled us to delineate and appreciate the success imparted by esthetics and function from the general well being imparted by treatment with dental implants. Social media could be used to positively improve responses in questionnaire based studies. Future studies using implant specific OHRQoL questionnaire may help to elicit unbiased patient perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…An increasing use of dental implants in metropolitan areas and among those with higher socioeconomic background was predicted by earlier studies on dental implant awareness in different regions of India. 5 , 7 The same is not true for second-tier cities and rural communities. Therefore, a questionnaire based cross sectional survey was conducted to check the awareness and acceptability of dental implants as a permanent solution for replacement of missing teeth.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing use of dental implants in metropolitan areas and among those with higher socioeconomic background was predicted by earlier studies on dental implant awareness in different regions of India. 5 , 7 The same is not true for second-tier cities and rural communities. Therefore, a questionnaire based cross sectional survey was conducted to check the awareness and acceptability of dental implants as a permanent solution for replacement of missing teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Dental implant therapy has been a well-established method to restore missing teeth [ 1 ]. Numerous studies have demonstrated that dental implants are able to increase patients’ chewing function, self-esteem, social life, and quality of life [ 2 , 3 ]. A global cross-sectional study indicated that not only are general practitioners beginning to perform implant therapy, but also those within 0–2 years of graduation had a higher percentage of placing their first implants despite acknowledging they were not yet proficient in implant practice [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The oral health impact profile questionnaire (OHIP-14) was developed with the aim of providing a measure of self-reported physical and psychological dysfunction and discomfort attributed to oral health status in quality of life (Slade, 1997;Paul et al, 2018).…”
Section: Discussionmentioning
confidence: 99%